Synthesis and Characterization of Macrocyclic Chiral Tröger’s Base Phenhomazine Candidates as Anticancer Agent - Ibrahim, Alhussein A.; Ali, Korany A.; Hafez, Naglaa A. Abdel; Elsayed, Mohamed A.; Mohamed, Khalid M. H.; Hosni, Hanaa M.; Amr, Abd El-Galil E.; Elsayed, Elsayed A. (Frontiers in Chemistry, 2021)
1,4,7,10-Tetraoxa[10](2,8)trögerophane 5 was synthesized from its ordinary reported precursors and using as starting material. Heating of 2 with p-nitrophenoxide afforded bis(p-nitrophenyl)ether 3, which was treated with hydrazine hydrate to give bis(p-aminophenyl)ether 4. Treatment of 4 with paraformaldehyde and triflouroacetic anhydride gave trögerophane 5. Reaction of 5 with trifluroacetic anhydride to afford phenhomazine derivative 6, which was treated with potassium carbonate to afford tetrahydrophenhomazine 7. Finally, reaction of 7 with phenacylchloride, bromoacetic acid, or ethyl bromoacetate in the presence of triethyl amine under reflux, afforded the corresponding macrocyclic compounds 8, 9 and 10, respectively. The synthesized trögerophane with some of its precursors and its newly synthesized phenhomazines derivatives were screened for anticancer activity, and 1,4,7,10-tetraoxa[10](2,8)trögerophane has shown a promising selectivity on colon cell line with IC50 = 92.7 µg/ml.